ANALYSIS OF CURRENT RATIO, QUICK RATIO, CASH RATIO, INWC RATIO ON THE FINANCIAL PERFORMANCE OF THE BEI CABLE SUB-SECTOR - Laili, Eka Fadhillatus; Amrozi, Ahmad Imam; Prayitno, Dwi Hari; Satiti, Abidah Dwi Rahma; Kurniyawati, Indah (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
This research aims to determine the financial performance of cable sub-sector companies listed on the IDX in 2015-2020 in fulfilling their short-term obligations in terms of current ratio, quick ratio, cash ratio and INWC ratio. This research uses quantitative descriptive methods. The research results show that the company's financial performance in terms of the current ratio is said to be relatively good. Judging from the quick ratio of PT. Jembo Cable Company Tbk and PT. Kabelindo Murni Tbk is said to be not good, PT. KMI Wire & Cable Tbk, PT. Supreme Cable Manufacturing and Commerce Tbk and PT. Voksel Electric Tbk is said to be relatively good. Financial performance in terms of the cash ratio is stated to be not good, PT. Supreme Cable Manufacturing and Commerce Tbk is said to be good. Financial performance is reviewed from PT's INWC ratio. Jembo Cable Company Tbk, PT. Kabelindo Murni Tbk is not good, PT. KMI Wire & Cable Tbk, PT. Supreme Cable Manufacturing and Commerce Tbk, PT. Voksel Electric Tbk was declared good.